The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1093/bioinformatics/btu746
|View full text |Cite
|
Sign up to set email alerts
|

GASS: identifying enzyme active sites with genetic algorithms

Abstract: GASS results were compared with those catalogued in the catalytic site atlas (CSA) in four different datasets and compared with two other methods: amino acid pattern search for substructures and motif and catalytic site identification. The results show GASS can correctly identify >90% of the templates searched. Experiments were also run using data from the substrate binding sites prediction competition CASP 10, and GASS is ranked fourth among the 18 methods considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 26 publications
0
24
0
7
Order By: Relevance
“…The tests reported in this section consider datasets of catalytic sites, although MeGASS can be also used for subtract binding site identification [10]. We start with catalytic sites because they are smaller and easier to deal with.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tests reported in this section consider datasets of catalytic sites, although MeGASS can be also used for subtract binding site identification [10]. We start with catalytic sites because they are smaller and easier to deal with.…”
Section: Resultsmentioning
confidence: 99%
“…In order to tackled these problems, we recently proposed GASS (Genetic Active Site Search) [10], which does not impose any restrictions such as those aforementioned and, above all, can precisely identify the chain where the residues of the active site are located. Difficulties in correctly identifying the chain where the active site residues are located is one of the main drawbacks of the current methods, as showed in [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another method that predicts active site pockets is AADS that uses geometric information on cavities in addition to physicochemical properties of residues . Some methods have implemented genetic algorithms, which use structural information as well as sequence and network based properties in combination with machine learning to identify active site residues . More recently, protein dynamics was also used as a predictor for active sites.…”
Section: Introductionmentioning
confidence: 99%
“…18 Some methods have implemented genetic algorithms, which use structural information as well as sequence and network based properties in combination with machine learning to identify active site residues. 19,20 More recently, protein dynamics was also used as a predictor for active sites. Glantz-Gashai and co-workers revealed that normal modes can expose active sites, and they used changes in solvent accessibilities to predict active site residues.…”
Section: Introductionmentioning
confidence: 99%